MENINGKATKAN KEPERCAYAAN DIRI ANAK DENGAN MEMBEDAH NILAI-NILAI YANG TERKANDUNG PADA DONGENG CINDELARAS - Muhammad Munawwir Shofiyulloh; Abdul Muhid (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2020)
Confidence in the culture, confidence in the private nation, confidence in the noble values that have been agreed ingrained in the heart is a good planting process used to save from the civilization of several nations. With the increasingly liberal era of globalization requires merging of values in local wisdom. One of the products of this local culture is the folklore from East Java, Cindelaras. The purpose of this study is to find the messages contained in fairy tales or folklore Cindelaras to increase children's confidence and revive old stories so that Indonesian cultures in any form, not eroded by other cultures. The results of the study after studying the research will discuss about what makes reading fairy tales to children increases their confidence, this is related to the values that can be taken from each of these tales. If examined one by one from each incident in a fairy tale, children will take more essence from it. On the other hand this is a step to involve local traditions and culture.